Conjecture and hypothesis: The importance of reality checks - Deamer, David (Beilstein Journal of Organic Chemistry, 2017)
In origins of life research, it is important to understand the difference between conjecture and hypothesis. This commentary explores the difference and recommends alternative hypotheses as a way to advance our understanding of how life can begin on the Earth and other habitable planets. As an example of how this approach can be used, two conditions have been proposed for sites conducive to the origin of life: hydrothermal vents in salty seawater, and fresh water hydrothermal fields associated with volcanic landmasses. These are considered as alternative hypotheses and the accumulating weight of evidence for each site is described and analyzed.
Keywords: hydrothermal fields; hydrothermal vents; origin of life; polymerization by condensation; protocells